Prospects for the application of project management in the public sector of Kazakhstan - A. E. Kartov (Экономика: стратегия и практика)
The article was written in order to develop specific proposals for the development of the project management system, in terms of improving the institutional and legal support, as well as improving the organization of the project office based on the analysis of the current state of work on the principles of project management in the public sector of Kazakhstan. In general, the concept of application of project management is considered from the point of view of the state planning system, which is currently functioning in the country. That is, the use of elements and tools of project management is imposed on the current law, namely in the part of documents that make up state planning. Thus, the article used not only an analytical approach, but also an informational one. The conclusion is made and substantiated about the need for an organization to reach a certain level of maturity before implementing project management. Specific proposals have also been made regarding amendments to the legal part. The architecture of a virtual project office, which is gaining its relevance recently, is described. The role of the executive secretary is also considered separately, it is proposed that this category be assigned to the position of special powers of the project manager. The following research methods were used: document analysis, case studies, deduction, generalization and concretization.